(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
As the world becomes green, it emphasizes the importance of adopting a sustainable, environmentally and socially beneficial lifestyle. A growing body of academic research on “going green” offers a new standpoint on the concept of Green Entrepreneurship. Green entrepreneurship aims to follow classic entrepreneurial ideals while providing additional benefits to society and the environment at the same time. The study explores the influence of factors, namely, entrepreneurial creativity, university green entrepreneurial support, green recognition, and green value variables, on green entrepreneurial intentions, along with the moderating role of gender, family income and family occupation among students. Data from 600 Undergraduate and Postgraduate students was collected using the survey method. For this purpose, a structured questionnaire with a five-point Likert scale was used. The statistical techniques applied to the dataset were confirmatory factor analysis and structural equation modeling using SPSS, AMOS, and process-Macro.